Meta-Analysis Approach to Measure the Effect of Integrated Nutrient Management on Crop Performance, Microbial Activity, and Carbon Stocks in Indian Soils - Padbhushan, Rajeev; Sharma, Sheetal; Kumar, Upendra; Rana, D.S.; Kohli, Anshuman; Kaviraj, Megha; Parmar, Brajendra; Kumar, Rajkishore; Annapurna, K.; Sinha, Abhas Kumar; Gupta, Vadakattu V.S.R. (Frontiers in Environmental Science, 2021)
Crop production has been declining in recent years due to inadequate management practices, creating considerable concern. These activities have also depleted soil organic matter stocks, resulting in a decrease in microbial activity and soil organic carbon (SOC) content.Moreover, even with minimal use of organic sources in cultivated land, soil carbon status deteriorated, particularly in subtropical climates. Integrated nutrient management (INM), a modified farming method, has effectively exploited organic and inorganic resources, increased the quality of soils and crops, and made farming more economically viable and sustainable.The aim of this study was to use meta-analysis to quantify the effects of INM on crop production, soil carbon, and microbial activity in Indian soils. During the years 1989 to 2018, data from various research studies in India, mainly on nutrient management in rice and wheat crops were collected.Meta-Win2.1 software was used to analyze the results, and significance was determined at p<0.05.The results showed that the yield of rice and wheat were 1.4 and 4.9% more in INM than in 100%NPK (N: nitrogen, P: phosphorous, and K: potassium), and that respective yields were comparatively higher in loamy soils (2.8%) and clayey soils (1.0%).The INM treatment increased SOC and microbial biomass carbon (MBC), resulting in improved overall soil quality. The SOC stock was increased by 23.8% in rice,15.1% in wheat,25.3% in loamy soils, and 14.4% in clayey soils in INM over 100%NPK. Microbial quotient (MQ) data showed significant trends between different management systems in both soil types, e.g.INM>100% NPK>No NPK. Due to more soil cracking and reduced aggregate stability in the rice field (greater short-term soil structural changes), the SOC stock loss in rice was higher than in wheat. The CO2 equivalent emissions were 7.9 Mg ha-1 higher in no NPK (control) than in 100%NPK, and 16.4Mg ha-1 higher in control than in the INM. In other words, INM increased soil carbon sequestration by 2.3Mg ha-1 as compared to using 100%NPK. Overall, the findings of this study show that INM could be an ideal model in India for improving crop production, increasing soil carbon sequestration, and improving microbial activity while remaining economically and environmentally sustainable.